Flexible heat-spreading and air-cooling films using nickel-electroplated nanotextured fibers. (14th December 2020) - Kim, Taegun; An, Seongpil; Park, Chanwoo; Choi, Jeehoon; Yarin, Alexander L.; Yoon, Sam S.
Graphical abstract: Highlights: Thin, flexible, wearable, heat-spreading, cooling films have been fabricated. The cooling films are decorated with highly nanotextured Ni mircrofibers. The Ni-electroplated microscale fibers could quickly spread heat over a solid medium. The cooling films could dissipate heat to the atmosphere via convective cooling. Abstract: Malfunctioning caused by hotspots in high-power and high-density microelectronics has been a major problem, particularly for miniaturized advanced portable electronic devices. The use of efficient heat spreaders or cooling films is a viable solution for mitigating the hotspot concern in high-power density electronic devices. In this study, we fabricated thin, flexible, wearable, heat-spreading cooling films decorated with highly nanotextured Ni microfibers. The Ni-electroplated microfibers could quickly spread heat over a solid medium and dissipate heat to the atmosphere via convective cooling. In the present parametric studies, the Ni electroplating time varied from 45 to 60 and 90 min. The optimal condition, which yielded the lowest thermal resistance and the highest heat transfer coefficient, was identified. The Ni microfibers were characterized using scanning electron microscopy, X-ray diffraction, and transmission electron microscopy analyses.